Pengaruh Nyanyian Liturgi "BBT" Terhadap Partisipasi Kaum Muda dalam Perayaan Ekaristi - Hermawan, Antonius Joko (Jurnal Teologi (Journal of Theology), 2017)
In 2009, Commission for Liturgy of the Archdiocese of Semarang published a liturgical songbook for the youth: Bernyanyilah Bagi Tuhan (BBT). The author is interested in answering a question: have liturgical songs in BBT responded to the needs of the youth and affected their understanding of faith? To answer this question, the author has conducted a field research by using qualitative research methods. To obtain relevant data, the authors conducted an in-depth interview with fifteen participants. The findings reveal positive signs that the BBT songs have met the needs of the youth through singing those songs for the youth. The songs also prove to affect their understanding of faith. Its significant influence is clearly seen from the participations of youth in various Eucharistic celebrations. Through those songs, young people are helped to express their faith physically and spiritually by way of singing in a Eucharist.